Dermatoglyphic Studies among the Dumagat-Remontado Tribal Population of the Philippines. (12th December 2012) - Gutierez, Sally B.; Lucenario, John Lou S.; Yebes, Mark Jason T.
Abstract : Dermatoglyphics is the study of dermal ridges. Since dermatoglyphic characters are recognized as a unique individual trait and follow a multifactorial or polygenic pattern of inheritance, it is necessary to understand the variations leading to this pattern. The present paper, through appropriate descriptive approach, has revealed the variation in the pattern of inheritance in the TFRCs of the Dumagat-Remontados from Puray, Rodriguez, Rizal, Philippines. The study also reported a large discrepancy on the total fingerprint ridge count among the Dumagat-Remontados compared to established researches. Also, the increased heterozygosity due to genetic admixture led to the dominant occurrence of the loop pattern (ulnar) in the fingerprints of this group of indigenous people as compared to few established data stating that the frequency of whorl patterns dominates the universal population and other Asian racial groups. In this study, a special feature on the fingerprint patterns of the pure Dumagat-Remontados was reported. Aside from the high frequency of loops and whorls, a distinct club dent, concluded to be a unique feature found among this tribal population, was noted from at least one of the fingers of the majority of the pure sample.